E-Learning Pembelajaran Ilustrasi Menggunakan Metode Iconix Process - Hutasuhut, Dedek Indra Gunawan; Ambiyar, A; Verawardina, Unung; Alfina, Ommi; Ginting, Erwin; Zaharani, Hetty (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
E-learning is an important advance in the modern education system. While an Illustration is an art of visual on writing artwork, drawing, painting, photography or another type on an art. Most People want to be an illustrator usually must learning their skill basic with self-taught or learning on art of school. However most people specifically for known illustration and want to learn their skill on art school but constrained with distance or time or another reason with their tools art. Until the most people can not got their skill with fast. By looking at this times with the Design Online Learning Of Education On Illustration At Website, which have contain more information and education about illustration and the illustrator can make easier for other to learning or to hone their skill with complete material which is came from most experience illustrator. The design will become a place of sharing content about illustration, it was built with PHP, and DBMS MySql. This research resulted in an e-learning application using Iconix process.